Akuisisi Bukti Digital Dan Deteksi Keaslian Citra Pada Whatsapp Menggunakan Metode NIST Dan ELA - Putra, Ikhwan Wiratama; Suharso, Aries; Rozikin, Chaerur (STIKOM Tunas Bangsa Pematangsiantar, 2021)
The growth of technology in the last 3 years has been very rapid, as is the growth of smartphone use. This growth is directly proportional to the crime cases that occur, especially in Indonesia. There were a total of 12,835 case complaints from 2018 to 2020, and the most cases were online fraud cases with 7,560 reports related to fraud on cyber patrol sites. One of the crimes that often occurs is online fraud cases using fictitious transfer receipts. This crime was committed using one of the short messaging applications, namely Whatsapp. After the crime was successfully carried out, the perpetrator then deleted the evidence in the form of the conversation along with a photo of the proof of the transfer using one of the features on WhatsApp. Therefore, this study aims to obtain or acquire evidence on the Whatsapp application using the NIST (National Institute of Standards and Technology) method and applying the ELA (Error Level Analysis) technique to analyze evidence in the form of images obtained to strengthen the evidence in court. In facilitating the investigation process, a forensic tool is needed. The forensic tools used in this research are Magnet Axiom and ForensicallyBeta. The final result obtained is that Magnet Axiom managed to find some evidence, including conversation messages, victim contacts, call history, profile photos of the perpetrators, and pictures. With the help of ForensicallyBeta tools, the obtained receipt image can be analyzed and identified that there has been a modification to the receipt.